Grow rich while you sleep: selection in experiments with voluntary participation - Pieter A. Gautier; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2006)
We use data from a promotion campaign of NH-Hoteles to study self-selection of participants in a gift-exchange experiment. The promotion campaign allowed guests to pay any non negative amount of money for a stay in one of 36 hotels in Belgium and the Netherlands. The data allow us to distinguish between 'regular guests', who booked prior to the announcement of the promotion campaign and guests who booked after the campaign was announced. During the promotion campaign we varied the posted price of a room that was communicated to the guests. Only the regular guests respond to the exogenous variation in the posted price and they pay substantially more on average. This different behavior cannot be explained by differences in satisfaction or observed compositional differences between both groups. We argue that the promotion campaign mainly attracted individuals who find it relatively unimportant to be viewed as prosocial.
urn:nbn:de:101:1-20090406252
Keywords: 330